Topical Treatment of Ulcerative Colitis using Enemas Containing 5-Aminosalicylic Acid and Beclomethasone Dipropionate. (1st November 1990) - Campieri, M; Gionchetti, P; Belluzzi, A; Tampieri, M; Brignola, C; Ferretti, M; Miglioli, M; Barbara, L
Abstract : 5-Aminosalicylic acid (5-ASA) enemas constitute a first-line therapy for patients with mild to moderate attacks of ulcerative colitis. To date, based on the results of different studies, 5-ASA enemas appear to be satisfactory in at least two-thirds of patients treated. Beclomethasone is one of the new corticosteroids which appear to have minimal systemic effects. The authors have assessed the efficacy of a four week course of 3 mg beclomethasone enemas compared to 2 g 5-ASA enemas in patients with ulcerative colitis. Preliminary analysis would suggest that both therapies are effective in more than 50% of cases.